Improved Fouling Resistance in Polysulfone-Based Ultrafiltration Membranes by the Addition of Polar Peptoid Oligomers Obtained from Ugi-4cr. Synthesis and Characterization - Martin-Trasancos, R; Martin-Trasancos, R (Elsevier Ltd, 2025)
This study explores the synthesis and characterization of eight polar peptoid oligomers obtained via the Ugi four-component reaction (Ugi-4CR), which were used as polar additives in the preparation of polysulfone membranes using the phase inversion technique. The membranes were characterized by morphology, porosity, hydrophilicity, and water permeability analysis and evaluated based on Bovine Serum Albumin (BSA) rejection. The results demonstrated that the addition of these oligomers with polar groups significantly improved the affinity of the membranes for water, thereby increasing their resistance to fouling. Pore size and porosity were found to vary depending on the concentration and structure of the oligomer added. The modified membranes exhibited reduced permeability but higher BSA rejection efficiency compared to the unmodified polysulfone membrane. These findings suggest that Ugi-4CR-derived oligomers represent an effective strategy to enhance the properties of ultrafiltration membranes, which could have valuable applications in water treatment and protein separation processes. © 2025 Elsevier Ltd